Pengaruh Lingkungan Kerja Bagi Tingkatan Kinerja Karyawan Restaurant (Y) Di Hotel (X) - Methania, Ribka (Peneliti.net, 2024)
Tourism is one of the most potential industries to grow in Indonesia, the hospitality industry is part of the service and service sector that has an important role in the tourism industry. Hotel X is a five-star hotel located in the city of Jakarta. This 33-story hotel was first inaugurated on February 1, 2001. In Jakarta, there are five-star hotels (5) such as Shangri-La Hotel, Le Meridien, Mandarin Hotel, Double-Tree Hotel and the x hotel. work environment factors, leadership factors can also affect a person's satisfaction at work. Leadership style is a method used by a leader to direct the behavior of others or subordinates in order to achieve a desired goal. desired goal. Leadership has a very positive effect on employee or employee job satisfaction. A good leader should be able to direct their employees well and clearly. If a leader cannot direct or set a good example to his employees, then employees will feel dissatisfied and the productivity of employees and companies will decrease. dissatisfied and the productivity of employees and the company will decrease.